Психологизм как художественный прием в творчестве Тома Стоппарда - Бокова, О. (Культура народов Причерноморья, 2013)
В этом исследовании впервые используется комплексный подход к изучению системы образов и психологичности сюжета пьес выдающегося британского драматурга. Комплексный подход заключает в себе традиционные и новые методы. Например, с помощью типологического и исторического подходов, исследуем эволюцию понятия психологизма в литературе. Интертекстуальный подход дает возможность выявить межтекстовые связи и отношения между текстом пьес «Настоящее», «Индийская туш», и текстами других авторов. Ключевые слова: психологизм, английская драматургия, театральнасть, психологический театр, современная интеллектуальная драма, Том Стоппард. У цiй статтi вперше використовується комплексний пiдхiд до вивчення системи образiв та психологiчнiсть сюжету п'єс визначного британського драматурга. Комплексний пiдхiд складається з традиційних і нових методів дослiдження проблеми. Наприклад, за допомогою типологічного та історичного підходів, досліджуємо еволюцію поняття психологізму в літературі. Інтертекстуальний підхід дає можливість виявити межтекстовi зв'язки п'єс «Справжнє», «Індійська туш" і текстами інших авторів. Ключові слова: психологiзм, англiська драматургiя, театральнiсть, психологiчний театр, сучасна iнтелектуальна драма, Том Стоппард. Тhe exposed author is an expert in arranging paradoxes, has the talent of wonderful interpretation of classics in literature, the brilliant virtuoso, who is prone to mimic and dramatize the reality. Earned his worldwide popularity and now he is taken for an outstanding and the epoch making author. The plays of Tom Stoppard are not only the entertainment for intellectuals but also deeply psychologically relevant pieces of art in which the problem of the relationship between people is touched upon. The topicality of the present research is determined by the fact that the works of this author attract the attention of not only wide range of appreciators and fans but also it is interesting for theatrical and literary critics. In this article the integrated approach is used to apprehend the depth of the system of the characters and the peculiarities of psychological arrange of the works of a brilliant English playwright. The integrated approach is consistent of traditional and new methods. Traditional methods are the following: typological, historical approach, comparative and stylistic ones. With the help of psychological and historical approach we can examine the evolution of the concept of psychologism in literature. The new methods are intertextual, psychological, analytical, phenomenological approach. Intertextual approach enables us to identify the intertextual connections and relations between the text of the play "The Real Thing", "Indian Ink" and texts written by the other authors. Keywords: psychologism, the English drama, theatricality, the psychological theatre, the modern intellectual drama, Tom Stoppard.